Self-assembled monomolecular layer material with asymmetric intermediate core and preparation method and application of self-assembled monomolecular layer material
By designing a self-assembled single-layer material based on asymmetric intermediate core structure as the hole transport layer, the acid corrosion, hygroscopic aging and performance attenuation caused by PEDOT:PSS materials in the prior art is solved, and a higher efficiency and more stable organic solar cells are achieved.
Patent Information
- Application Number
- CN202411879122.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The commonly used hole transport layer material PEDOT:PSS in existing organic solar cells has performance attenuation problems under external pressure such as acid corrosion, hygroscopic aging and photothermal pressure, resulting in insufficient device efficiency and stability.
Design and develop self-assembled single-layer materials based on asymmetric intermediate core structures, and form a uniform single-layer by reacting anchor groups with the surface of the ITO substrate, optimize the energy level arrangement between the ITO and the active layer, and improve the hole extraction ability.
It significantly improves the energy conversion efficiency and stability of organic solar cells, reduces production costs, and improves the water and oxygen stability of the device.
Smart Images

Figure CN119684362A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar cells, and in particular relates to a self-assembled monolayer material with an asymmetric intermediate core, a preparation method and an application thereof. Background Art
[0002] Solar energy is a clean and renewable energy source. Using solar cells to generate electricity is an effective way to solve the current energy crisis and environmental pollution problems. As early as 1954, Bell Labs developed the first silicon solar cell in history. Up to now, although silicon solar cells have occupied a considerable market share, their production cost is high and the power conversion efficiency (PCE) is approaching the theoretical limit. Therefore, it is urgent to develop a new generation of low-cost and high-efficiency photovoltaic technology. Organic solar cells (OSCs) have the advantages of intrinsic flexibility, light weight and low processing cost, which have attracted the attention of more and more scientific researchers. In the past decade, the PCE of OSC has developed rapidly and has reached 19.2% certified by the National Renewable Energy Laboratory.
[0003] OSC can be divided into pin structure and nip structure according to the different electrode polarities. The pin structure OSC is composed of indium tin oxide (ITO) substrate, hole transport layer (HTL), active layer, electron transport layer (ETL) and metal electrode (Ag) in sequence. The hole transport layer is mainly responsible for transporting photogenerated holes and blocking photogenerated electrons, which has an important influence on the efficiency and stability of the device. At present, the commonly used hole transport layer material for pin structure OSC is poly (3, 4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), but it has the following problems: (1) PEDOT:PSS has strong acidity and will corrode the ITO substrate, thereby causing In 3+ Invasion of the hole transport layer and even the active layer will cause serious damage to the device performance; (2) PEDOT:PSS is highly hygroscopic and will absorb water and oxygen in the air, accelerating the aging of the device; (3) Under external pressure such as light and heat, phase separation is likely to occur, causing the device performance to gradually decay. Therefore, designing and developing low-cost, high-performance HTL materials with good compatibility with the active layer is crucial to further improve the efficiency and stability of OSCs.
[0004] Self-assembled monolayers (SAMs) can be anchored on the ITO surface to form a uniform monolayer through dehydration condensation of anchoring groups (such as phosphonic acid, sulfonic acid, boric acid, carboxyl, etc.) with the hydroxyl groups on the surface of the ITO substrate, which is expected to improve the operating stability of the corresponding device. SAMs can adjust the work function of ITO and optimize the energy level arrangement between ITO and the active layer, thereby effectively extracting holes; and have high light transmittance, which helps to obtain higher short-circuit current and achieve higher PCE. In addition, SAMs have low synthesis cost, small dosage, and are easy to prepare, which has great potential in practical production. The above advantages have prompted more and more researchers to focus their research on the design and development of SAMs. It is worth noting that most of the SAMs commonly used in organic photovoltaic devices are based on symmetrical intermediate core structures. These SAMs have small dipole moments and show poor hole extraction ability, which affects the device performance. Therefore, the development of SAMs based on asymmetric intermediate core structures is expected to improve the hole extraction ability and further improve the device efficiency. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a self-assembled monolayer material with an asymmetric intermediate core, which has a simple synthesis method, low cost, and is easy to prepare on a large scale; the second purpose of the present invention is to provide a method for preparing the above-mentioned self-assembled monolayer material with an asymmetric intermediate core; the third purpose of the present invention is to provide an application of the above-mentioned self-assembled monolayer material with an asymmetric intermediate core.
[0006] Technical solution: The present invention provides a self-assembled monolayer material with an asymmetric intermediate core, wherein the structural formula of the asymmetric intermediate core is:
[0007] Wherein, X is H, Br, Cl or F;
[0008] The general formula of the self-assembled monolayer material is:
[0009] Wherein, n is 1-3, and R is a phosphonic acid group, a sulfonic acid group, a boronic acid group or a carboxylic acid group.
[0010] Preferably, the self-assembled monolayer material includes (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid, and the structural formula is: (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid, the structural formula is: (2-(3H-Benzo[e]indol-3-yl)ethyl)phosphonic acid, the structural formula is: and (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid, the structural formula is:
[0011] The preparation method of the self-assembled monolayer material with an asymmetric intermediate core, wherein n is 2 and R is a phosphonic acid group, is prepared as follows:
[0012] (1) and sodium hydride are dissolved in a solvent, stirred and reacted at room temperature under a protective atmosphere, and then 2-bromoethyl diethyl phosphate is added and heated to react. After the reaction mixture is completed, the solvent is removed, and the organic phase is extracted with ethyl acetate, and then the organic phase is dried with a dehydrating agent, and the crude product is obtained by distillation under reduced pressure;
[0013] (2) The crude product is dissolved in a reaction solvent, trimethylsilyl bromide is added dropwise, and the mixture is fully reacted at room temperature in a protective atmosphere. After the reaction is completed, a quencher is added and stirring is continued. After removing part of the methanol by vacuum distillation, distilled water is added dropwise until the solution is opaque. After stirring overnight, the product is filtered out, washed with water, and dried.
[0014] Furthermore, in step (1), the solvent is dimethylformamide or tetrahydrofuran, and the conditions for the heating reaction are: the reaction temperature is 50-80° C., and the reaction time is 5-15 h.
[0015] Further, in step (1), the 2-bromoethyl diethyl phosphate is relative to The molar equivalent is 1.0-3.0eq, and the sodium hydride is relative to The molar equivalent is 1.0-3.0eq.
[0016] Furthermore, in step (1), the dehydrating agent is anhydrous sodium sulfate or anhydrous magnesium sulfate, and the method of removing the solvent is: placing the reaction mixture in a NaCl aqueous solution and mixing it thoroughly.
[0017] Furthermore, in step (2), the reaction solvent is anhydrous dichloromethane, 1,4-dioxane or tetrahydrofuran, the molar equivalent of trimethylsilyl bromide relative to the crude product is 10-15 eq; and the quenching agent is methanol.
[0018] The application of the self-assembled monolayer material with an asymmetric intermediate core in the preparation of organic solar cells and perovskite solar cells with a pin structure.
[0019] Furthermore, the organic solar cell and perovskite solar cell of the PIN structure include, from bottom to top, a metal oxide electrode, a hole transport layer, an active layer, an electron transport layer and a top electrode, and the material used for the hole transport layer is the self-assembled monolayer material with the asymmetric intermediate core.
[0020] Furthermore, the preparation steps of the battery are:
[0021] (a) The cleaned ITO glass was treated with UV-ozone to improve wettability and used as a metal oxide electrode;
[0022] (b) preparing an isopropanol solution containing the self-assembled monolayer material having an asymmetric intermediate core;
[0023] (c) spin coating the above solution onto an ITO substrate and annealing;
[0024] (d) spin coating the active layer solution and the PNDIT-F3N solution in sequence and annealing to obtain the active layer and the electron transport layer;
[0025] (e) finally, Ag is deposited by thermal evaporation to form a top electrode; wherein, in step (a), the UV-ozone treatment time is 10-20 min; in step (b), the molar concentration of the self-assembled monolayer material having an asymmetric intermediate core is 0.1-0.8 mg / mL, preferably 0.3-0.5 mg / mL; in step (c), the spin coating speed is 1000-5000 rpm, preferably 3000-5000 rpm; the duration is 15-50 s, preferably 30-50 s; in step (e), the thickness of the Ag electrode is 10-100 nm, preferably 70-100 nm.
[0026] Invention principle: Asymmetric intermediate core structures often have larger dipole moments than common symmetric intermediate core structures, and larger dipole moments help improve hole extraction capabilities. Therefore, designing SAMs materials based on asymmetric intermediate core structures helps further improve the energy conversion efficiency of solar cells.
[0027] Beneficial effects: Compared with the hole transport layer material (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) commonly used in existing organic solar cells, the SAMs based on the asymmetric intermediate core structure prepared by the present invention have significant advantages in many aspects as hole transport layer materials: (1) SAMs based on the asymmetric intermediate core structure absorb less light in the near-infrared region, which allows the active layer to receive more photons and thus cause exciton dissociation, thereby improving PCE; (2) PEDOT:PSS has strong acidity and will corrode the ITO substrate, thereby causing In 3+Invasion of the hole transport layer or even the active layer can cause serious damage to the device performance, while the chemical properties of SAMs based on the asymmetric intermediate core structure are stable and will not cause the above problems; (3) PEDOT:PSS has high hygroscopicity and easily absorbs water and oxygen in the air, accelerating device aging, while SAMs based on the asymmetric intermediate core structure have good hydrophobicity and can greatly improve the water and oxygen stability of the device. Therefore, the OSC prepared by using SAMs based on the asymmetric intermediate core structure as HTL has significantly improved the efficiency and stability compared with the device prepared by PEDOT:PSS; the development of these new small molecule materials not only effectively improves the performance of OSC, but also provides important inspiration for reducing the production cost of OSC and promoting the commercialization of OSC. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of BACz prepared in Example 1 of the present invention;
[0029] Figure 2 The carbon NMR spectrum of BACz prepared in Example 1 of the present invention;
[0030] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of 2Br-BACz prepared in Example 2 of the present invention;
[0031] Figure 4 The carbon NMR spectrum of 2Br-BACz prepared in Example 2 of the present invention;
[0032] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of BEId prepared in Example 3 of the present invention;
[0033] Figure 6 This is the carbon NMR spectrum of BEId prepared in Example 3 of the present invention;
[0034] Figure 7 This is the hydrogen nuclear magnetic resonance spectrum of Br-BEId prepared in Example 4 of the present invention;
[0035] Figure 8 This is the carbon NMR spectrum of Br-BEId prepared in Example 5 of the present invention;
[0036] Fig. 9 Graph showing the performance test results of different organic solar cells prepared in Example 5;
[0037] Fig.10 This is a water contact angle test diagram of different hole transport layer materials prepared in Example 5. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments and drawings.
[0039] Example 1
[0040] The synthesis of the self-assembled monolayer material (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid (BACz) provided in this embodiment includes the following two steps:
[0041] (1) Synthesis of diethyl (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonate:
[0042] 11H-benzo[a]carbazole (0.5 g, 2.30 mmol) was dissolved in 10 mL of dimethylformamide, cooled to 0 °C, sodium hydride (92.1 mg, 2.30 mmol) was slowly added, stirred at room temperature for 30 min, then 2-bromoethyl diethyl phosphate (0.56 g, 2.30 mmol) was slowly added dropwise and the temperature was raised to 70 °C for overnight reaction. After the plate reaction was complete, the reaction mixture was cooled to room temperature, poured into a NaCl aqueous solution, and extracted with ethyl acetate. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: ethyl acetate = 1:2) to obtain a pale yellow solid (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid diethyl ester (0.68 g, 77%). 1 HNMR (400MHz, CDCl3): 8.54 (d, J=8.5Hz, 1H), 8.16 (t, 2H), 8.05 (d, J=6.7Hz, 1H), 7.68 (d, J=8.5Hz, 1H), 7.64-7.59 ( m, 2H), 7.56-7.49 (m, 2H), 7.33 (t, 1H), 5.14-5.09 (m, 2H), 4.26-4.12 (m, 4H), 2.50-2.42 (m, 2H), 1.40-1.37 (m, 6H). 13 CNMR (125MHz, CDCl3): 139.75, 133.88, 133.64, 129.79, 125.83, 125.05, 124.72, 123.31, 122.12, 1 21.43, 121.06, 120.02, 119.77, 119.67, 119.17, 108.88, 62.08, 62.01, 40.13, 27.37, 16.56, 16.50.
[0043] The reaction formula is as follows:
[0044]
[0045] (2) Synthesis of the compound (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid:
[0046] Dissolve diethyl (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonate (0.5 g, 1.31 mmol) in 10 mL of dichloromethane, slowly add trimethylsilyl bromide (2.01 g, 13.1 mmol), and react at room temperature overnight. After the reaction is complete, add methanol and continue stirring for 10 min. Then add distilled water until the solution is opaque, filter out the product, and dry to obtain a white solid (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid (0.29 g, 67%). 1 HNMR (400MHz, DMSO-d6): 8.63 (d, J=8.4Hz, 1H), 8.31-8.25 (m, 2H), 8.12 (d, J=6.7Hz, 1H), 7.7 4-7.64 (m, 3H), 7.60 (t, 1H), 7.53 (t, 1H), 7.31 (t, 1H), 5.04-5.00 (m, 2H), 2.28-2.09 (m, 2H). 13 CNMR (125MHz, DMSO-d6): 139.87, 133.85, 133.61, 129.91, 126.45, 125.57, 125.36, 12 2.92, 122.17, 122.01, 121.05, 120.26, 120.23, 119.79, 119.21, 109.74, 40.65, 29.77. MALDI-TOF-MS m / z: [MH] - calcd.for C 18 H 16 NO3P, 324.0789; found, 324.0794.
[0047] The reaction formula is as follows:
[0048]
[0049] Example 2
[0050] The synthesis of the self-assembled monolayer material (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid (2Br-BACz) provided in this embodiment includes the following two steps:
[0051] (1) Synthesis of diethyl (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonate:
[0052] 5,8-dibromo-11H-benzo[a]carbazole (0.5 g, 1.33 mmol) was dissolved in 10 mL of dimethylformamide, cooled to 0 °C, sodium hydride (53.3 mg, 1.33 mmol) was slowly added, stirred at room temperature for 30 min, and then 2-bromoethyl diethyl phosphate (0.33 g, 1.33 mmol) was slowly added dropwise, and then the temperature was raised to 70 °C for overnight reaction. After the reaction was complete, it was cooled to room temperature, the reaction mixture was poured into a NaCl aqueous solution, and extracted with ethyl acetate. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: ethyl acetate = 1:2) to obtain a pale yellow solid (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid diethyl ester (0.58 g, 81%). 1 HNMR (400MHz, CDCl3): 8.47-8.44 (m, 2H), 8.35 (s, 1H), 8.14 (d, J=1.8Hz, 1H), 7.66-7.59 (m, 2H), 7.55-7.52 (m, 1H), 7.42 (d, J=8.8Hz, 1H), 5.03-4.97 (m, 2H), 4.16-4.03 (m, 4H), 2.39-2.30 (m, 2H), 1.31-1.27 (m, 6H). 13 CNMR (125MHz, CDCl3): 138.47, 133.87, 131.11, 129.24, 128.25, 126.81, 126.31, 124.00, 123.08, 1 22.93, 122.36, 121.68, 119.01, 114.65, 113.35, 110.65, 62.16, 62.10, 40.37, 27.20, 16.54, 16.48.
[0053] The reaction formula is as follows:
[0054]
[0055] (2) Synthesis of the compound (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid:
[0056] Dissolve diethyl (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonate (0.5 g, 0.93 mmol) in 10 mL of dichloromethane, slowly add trimethylsilyl bromide (1.42 g, 9.3 mmol), and react overnight at room temperature. After the reaction is complete, add methanol and continue stirring for 10 min. Then add distilled water until the solution is opaque, filter out the product, and dry to obtain a white solid (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid (0.27 g, 61%). 1 H NMR (400MHz, DMSO-d6): 8.23 (d, J=8.1Hz, 1H), 7.91 (d, J=9.6Hz, 1H), 7.62 (t, 2H), 7.51 (t, 1H), 7.47 (d, J=3.1Hz, 1H), 7.38 (t, 1H), 7.05 (d, J=3.1Hz, 1H), 4.48-4.42 (m, 2H), 2.15-2.07 (m, 2H). 13 CNMR (125MHz, DMSO-d6): 138.85, 134.15, 130.68, 128.56, 128.48, 127.55, 127.28, 12 4.25, 123.92, 123.09, 123.06, 123.00, 118.83, 113.75, 112.95, 112.24, 41.52, 29.53. MALDI-TOF-MS m / z: [MH] - calcd.for C 18 H 14 Br2NO3P, 481.8979; found, 481.8997.
[0057] The reaction formula is as follows:
[0058]
[0059] Embodiment 3:
[0060] The synthesis of the self-assembled monolayer material (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonic acid (BEId) provided in this embodiment includes the following three steps:
[0061] (1) Synthesis of compound 3H-benzo[e]indole:
[0062] 2-aminonaphthalene (1g, 6.98mmol), Pt / Al2O3 (0.46g, 1.7mol%), and ZnO dispersion (77μL, 4.5mol%) were dissolved in ethylene glycol and heated under reflux at 185°C for overnight reaction. After the reaction was complete, the reaction mixture was cooled to room temperature, poured into a NaCl aqueous solution, and extracted with dichloromethane. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: dichloromethane = 2:1) to obtain a white flocculent solid 3H-benz[e]indole (0.95g, 81%). 1 HNMR (400MHz, CDCl3): 8.39 (s, 1H), 8.34 (d, J=8.2Hz, 1H), 8.00 (d, J=8.1Hz, 1H), 7 .71-7.62 (m, 2H), 7.58-7.48 (m, 2H), 7.28 (t, J=2.8Hz, 1H), 7.17 (t, J=2.6Hz, 1H). 13 CNMR (125MHz, CDCl3): 132.2, 129.2, 128.6, 128.3, 125.9, 123.4, 123.1, 123.0, 122.8, 122.3, 112.8, 101.9.
[0063] The reaction formula is as follows:
[0064]
[0065] (2) Synthesis of the compound diethyl (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonate:
[0066] 3H-Benzo[e]indole (0.5 g, 2.99 mmol) was dissolved in 10 mL of dimethylformamide, cooled to 0°C, sodium hydride (119.6 mg, 2.99 mmol) was slowly added, and the mixture was stirred at room temperature for 30 min. Then 2-bromoethyl diethyl phosphate (0.73 g, 2.99 mmol) was slowly added dropwise and the mixture was heated to 70°C for overnight reaction. After the reaction was complete, the mixture was cooled to room temperature, and the reaction mixture was poured into a NaCl aqueous solution and extracted with ethyl acetate. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: ethyl acetate = 1:2) to obtain a light yellow liquid (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonic acid diethyl ester (0.84 g, 85%). 1HNMR (400MHz, CDCl3): 8.28 (d, J=8.5Hz, 1H), 7.96 (d, J=6.8Hz, 1H), 7.69 (d, J=8.6Hz, 1H), 7.57-7.50 (m, 2H), 7.49-7.45 (m, 1 H), 7.13 (d, J=3.0Hz, 1H), 6.61 (d, J=3.0Hz, 2H), 4.90-4.84 (m, 2H), 4.20-4.06 (m, 4H), 2.45-2.37 (m, 2H), 1.36-1.31 (m, 6H). 13 CNMR (125MHz, CDCl3): 131.45, 129.54, 128.56, 128.20, 126.54, 125.70, 123.39, 1 22.63, 121.45, 121.19, 120.20, 103.07, 62.03, 61.97, 44.50, 28.49, 16.50, 16.44.
[0067] The reaction formula is as follows:
[0068]
[0069] (3) Synthesis of the compound (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonic acid:
[0070] Dissolve diethyl (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonate (0.5 g, 1.51 mmol) in 10 mL of dichloromethane, slowly add trimethylsilyl bromide (2.31 g, 15.1 mmol), and react at room temperature overnight. After the reaction is complete, add methanol and continue stirring for 10 min. Then, add distilled water until the solution is opaque, filter out the product, and dry to obtain a white solid (2-(3H-benzo[e]indol-3-yl)ethyl)phosphonic acid (0.25 g, 61%). 1 H NMR (400MHz, DMSO-d6): 8.16 (d, J=8.1Hz, 2H), 7.55 (d, J=9.6Hz, 2H), 7.48 (t, 2H), 7.22 (t, 2H), 4.58-4.52 (m, 2H), 2.07-1.98 (m, 2H). 13 CNMR (125MHz, DMSO-d6): 138.83, 134.12, 130.66, 128.46, 127.53, 127.26, 123.9, 122.97, 118.81, 113.72, 112.93, 112.22, 41.49, 29.5. MALDI-TOF-MS m / z: [MH] - calcd.for C14 H 14 NO3P, 274.0632; found, 274.0637.
[0071] The reaction formula is as follows:
[0072]
[0073] Example 4: The synthesis of the self-assembled monolayer material (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid (Br-BEId) provided in this example includes the following three steps:
[0074] (1) Synthesis of compound 7-bromo-3H-benzo[e]indole:
[0075] 6-Bromo-2-aminonaphthalene (1 g, 4.50 mmol), Pt / Al2O3 (0.30 g, 1.7 mol%), and ZnO dispersion (50 μL, 4.5 mol%) were dissolved in ethylene glycol and heated under reflux at 185°C for overnight reaction. After the reaction was complete, the reaction mixture was cooled to room temperature, poured into a NaCl aqueous solution, and extracted with dichloromethane. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: dichloromethane = 4:1) to obtain a white flocculent solid 7-bromo-3H-benzo[e]indole (0.76 g, 84%). 1 HNMR (400MHz, CDCl3): 8.39 (s, 1H), 8.34 (d, J=8.2Hz, 1H), 8.00 (d, J=8.1Hz, 1H), 7 .71-7.62 (m, 2H), 7.58-7.48 (m, 2H), 7.28 (t, J=2.8Hz, 1H), 7.17 (t, J=2.6Hz, 1H). 13 CNMR (125MHz, CDCl3): 132.2, 129.2, 128.6, 128.3, 125.9, 123.4, 123.1, 123.0, 122.8, 122.3, 112.8, 101.9.
[0076] The reaction formula is as follows:
[0077]
[0078] (2) Synthesis of the compound diethyl (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonate:
[0079] 7-bromo-3H-benzo[e]indole (0.5 g, 2.03 mmol) was dissolved in 10 mL of dimethylformamide, cooled to 0°C, sodium hydride (81.26 mg, 2.03 mmol) was slowly added, stirred at room temperature for 30 min, and then 2-bromoethyl diethyl phosphate (0.50 g, 2.03 mmol) was slowly added dropwise, and then the temperature was raised to 70°C for overnight reaction. After the plate reaction was complete, it was cooled to room temperature, and the reaction mixture was poured into a NaCl aqueous solution and extracted with ethyl acetate. The organic phase was then dried with anhydrous sodium sulfate, and then distilled under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (solvent polarity was, petroleum ether: ethyl acetate = 1:2) to obtain a light yellow liquid (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid diethyl ester (0.63 g, 75%). 1 HNMR (400MHz, CDCl3): 8.17 (d, J=8.7Hz, 1H), 8.08 (d, J=2.0Hz, 1H), 7.63-7.60 (m, 1H), 7.56-7.52 (m, 2H), 7.23 (d , J=3.1Hz, 1H), 7.01 (d, J=3.1Hz, 1H), 4.55-4.50 (m, 2H), 4.10-4.03 (m, 4H), 2.36-2.28 (m, 2H), 1.30-1.26 (m, 6H). 13 CNMR (125MHz, CDCl3): 133.08, 131.37, 130.57, 128.96, 127.78, 126.02, 124.67, 1 23.37, 121.75, 116.76, 111.87, 101.08, 62.02, 61.96, 40.79, 28.43, 16.43, 16.37.
[0080] The reaction formula is as follows:
[0081]
[0082] (3) Synthesis of the compound (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid:
[0083] Dissolve diethyl (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonate (0.5 g, 1.22 mmol) in 10 mL of dichloromethane, slowly add trimethylsilyl bromide (1.87 g, 12.2 mmol), and react at room temperature overnight. After the reaction is complete, add methanol and continue stirring for 10 min. Then, add distilled water until the solution is opaque, filter out the product, and dry to obtain a white solid (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid (0.27 g, 63%). 1HNMR (400MHz, CDCl3): 8.08-8.04(m, 2H), 7.61-7.58(m, 1H), 7.53-7.50(m, 2H), 7 .21 (d, J=3.1Hz, 1H), 6.99 (d, J=3.1Hz, 1H), 4.55-4.50 (m, 2H), 2.36-2.28 (m, 2H). 13 CNMR (125MHz, CDCl3): 132.06, 130.51, 130.34, 128.88, 126.85, 126.02, 124.67, 123.60, 121.75, 116.76, 111.87, 101.08, 40.79, 28.43. MALDI-TOF-MS m / z: [MH] - calcd.For C 14 H 13 BrNO3P, 351.9737; found, 351.9743.
[0084] The reaction formula is as follows:
[0085]
[0086] Example 5
[0087] The four SAMs based on asymmetric intermediate core structure prepared in Examples 1 to 4 were used as hole transport layers to prepare pin structure organic solar cells, whose structure from bottom to top was metal oxide electrode, hole transport layer, organic active layer, electron transport layer and metal electrode.
[0088] The specific preparation steps are as follows:
[0089] (a) The ITO glass was ultrasonically cleaned in a cleaning solution, deionized water, acetone and isopropanol in sequence for 15 min, and then dried in a vacuum oven. The dried ITO glass was treated with UV-ozone for 15 min to improve wettability; SAMs based on an asymmetric intermediate core structure were dissolved in isopropanol at a concentration of 0.5 mg / mL and stirred for 30 min. After stirring, 40 μL of the SAMs solution based on the asymmetric intermediate core structure was spin-coated on an ITO substrate at a speed of 3000 rpm for 30 s, and annealed on a hot stage at 100° C. for 10 min to prepare a hole transport layer;
[0090] (b) PM6 and Y6 were weighed in a ratio of PM6:Y6=1:1 (mass ratio), and then dissolved in chloroform at a concentration of 14 mg / mL and stirred for 30 min. After stirring, 15 μL of the active layer solution was dynamically spin-coated onto the SAMs based on the asymmetric intermediate core structure, and then spin-coated at a speed of 3000 rpm for 30 s, and then annealed at 80 °C on a hot stage for 5 min to prepare the active layer.
[0091] (c) PDIN was dissolved in ultra-dry methanol at 0.5 mg / mL and stirred for 30 min. After stirring, 40 μL of PDIN solution was spin-coated on the active layer, and then spin-coated at 3000 rpm for 30 s to prepare the electron transport layer. Finally, a 120 nm thick Ag electrode was thermally evaporated onto the prepared film.
[0092] The structures of the four SAMs products based on asymmetric intermediate core structures prepared in Examples 1 to 4 were determined by nuclear magnetic resonance. The results are as follows: Figure 1-Figure 8 shown.
[0093] The prepared organic photovoltaic device was tested using a xenon lamp solar simulator (the test light intensity was AM 1.5G, 100 mW cm -2 The obtained JV curve is as follows Fig. 9 As shown in Figure A), the PCEs of the four devices based on the asymmetric intermediate core structure SAMs are 18.0%, 18.1%, 18.6%, and 18.9%, respectively, which are all higher than the efficiency of the device based on the symmetric intermediate core structure 2PACz 17.7%. In addition, the prepared device based on the asymmetric intermediate core structure SAMs still maintains more than 95% of the initial efficiency after being stored in air for 480h ( Fig. 9 The efficiency of the devices based on PEDOT:PSS stored under the same conditions has decayed to 34.0% of the initial efficiency after 360h of storage. The above results show that the four new SAMs based on asymmetric intermediate core structure have significantly improved the device efficiency and stability compared with PEDOT:PSS.
[0094] The hydrophobicity of SAMs based on asymmetric meso-core structures was tested using a contact angle meter. Fig.10), it can be seen from the water contact angle diagram that the water contact angles of ITO / BEId, ITO / Br-BEId, ITO / BACz and ITO / 2Br-BACz are 61.44°, 71.26°, 72.12° and 79.54° respectively, which are significantly higher than ITO / PEDOT:PSS (25.59°). Therefore, the four SAMs based on asymmetric intermediate core structure prepared in Examples 1 to 4 can give the ITO electrode good hydrophobicity, thereby helping to improve the stability of the device.
Claims
1. A self-assembled monolayer material with an asymmetric intermediate core, characterized in that: The structural formula of the asymmetric intermediate core is: Wherein, X is H, Br, Cl or F; The general formula of the self-assembled monolayer material is: Wherein, n is 1-3, and R is a phosphonic acid group, a sulfonic acid group, a boronic acid group or a carboxylic acid group.
2. The self-assembled monolayer material according to claim 1, characterized in that: The self-assembled monolayer material includes (2-(11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid, and the structural formula is: (2-(5,8-dibromo-11H-benzo[a]carbazole-11-yl)ethyl)phosphonic acid, the structural formula is: (2-(3H-Benzo[e]indol-3-yl)ethyl)phosphonic acid, the structural formula is: and (2-(7-bromo-3H-benzo[e]indol-3-yl)ethyl)phosphonic acid, the structural formula is:
3. A method for preparing the self-assembled monolayer material with an asymmetric intermediate core according to claim 1, characterized in that: The n is 2, R is a phosphonic acid group, and the preparation steps are as follows: (1) and sodium hydride are dissolved in a solvent, stirred and reacted at room temperature under a protective atmosphere, and then 2-bromoethyl diethyl phosphate is added and heated to react. After the reaction mixture is completed, the solvent is removed, and the organic phase is extracted with ethyl acetate, and then the organic phase is dried with a dehydrating agent, and the crude product is obtained by distillation under reduced pressure; (2) The crude product is dissolved in a reaction solvent, trimethylsilyl bromide is added dropwise, and the mixture is fully reacted at room temperature in a protective atmosphere. After the reaction is completed, a quencher is added and stirring is continued. After removing part of the methanol by vacuum distillation, distilled water is added dropwise until the solution is opaque. After stirring overnight, the product is filtered out, washed with water, and dried.
4. The method according to claim 3, characterized in that: In step (1), the solvent is dimethylformamide or tetrahydrofuran, and the conditions for the heating reaction are: the reaction temperature is 50-80° C., and the reaction time is 5-15 h.
5. The method according to claim 3, characterized in that: In step (1), the 2-bromoethyl diethyl phosphate is relative to The molar equivalent is 1.0-3.0eq, and the sodium hydride is relative to The molar equivalent is 1.0-3.0eq.
6. The method according to claim 3, characterized in that: In step (1), the dehydrating agent is anhydrous sodium sulfate or anhydrous magnesium sulfate, and the method for removing the solvent is: placing the reaction mixture in a NaCl aqueous solution and mixing it thoroughly.
7. The method according to claim 3, characterized in that: In step (2), the reaction solvent is anhydrous dichloromethane, 1,4-dioxane or tetrahydrofuran, the molar equivalent of trimethylsilyl bromide relative to the crude product is 10-15eq; and the quenching agent is methanol.
8. Use of the self-assembled monolayer material with an asymmetric intermediate core according to any one of claims 1 to 2 in preparing organic solar cells and perovskite solar cells with a pin structure.
9. The use according to claim 8, characterized in that: The PIN structured organic solar cell and perovskite solar cell include, from bottom to top, a metal oxide electrode, a hole transport layer, an active layer, an electron transport layer and a top electrode. The material used for the hole transport layer is the self-assembled monolayer material with an asymmetric intermediate core as described in claim 1.
10. The use according to claim 9, characterized in that: The preparation steps of the battery are: (a) The cleaned ITO glass was treated with UV-ozone to improve wettability and used as a metal oxide electrode; (b) preparing an isopropanol solution containing the self-assembled monolayer material having an asymmetric intermediate core according to claim 1; (c) spin coating the above solution onto an ITO substrate and annealing; (d) spin coating the active layer solution and the PNDIT-F3N solution in sequence and annealing to obtain the active layer and the electron transport layer; (e) finally, Ag is deposited by thermal evaporation to form a top electrode; wherein, in step (a), the UV-ozone treatment time is 10-20 min; in step (b), the molar concentration of the self-assembled monolayer material with an asymmetric intermediate core is 0.1-0.8 mg / mL; in step (c), the spin coating speed is 1000-5000 rpm; the duration is 15-50 s; in step (e), the thickness of the Ag electrode is 10-100 nm.
Citation Information
Patent Citations
Preparation of perovskite solar cell based on self-assembly micromolecule one-step spin coating
CN116193942A
Self-assembled monomolecular layer hole transport material based on diphenylamine and synthesis method and application thereof
CN116655682A
Self-assembled monomolecular layer hole transport material containing diphosphonic acid terminal group and preparation method and application thereof
CN117567513A
Cited By
Compound based on imino structure and preparation method and application thereof
CN121248671A
Compounds based on imino structures, methods for their preparation and use
CN121248671B
N, N-bis (2-phosphonoethyl) arylamine and preparation method thereof
CN121319049A
3-hydroxy-4-(4-pyridylazo) anilino-N, N-bis (ethyl-2-phosphonic acid) and preparation method thereof
CN121362214A
2-(3-hydroxy-4-(N, N-bis (2-phosphonoethyl) amino) phenyl) benzotriazole and preparation method thereof
CN121426840A